2013
DOI: 10.1371/journal.pone.0071514
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Spinal Perineurial (Tarlov) Cysts among East-European Patients

Abstract: The spinal perineurial cyst (Tarlov) is a dilatation between the perineurium and endoneurium of spinal nerve roots, located at level of the spinal ganglion and filled with cerebrospinal fluid but without communication with the perineurial subarachnoid space. The aim of the study was to evaluate it incidence among East-European patients. The retrospective data collected during various magnetic resonance spinal examinations and stored on the picture archiving and communication system was analyzed for an incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 12 publications
1
32
0
4
Order By: Relevance
“…It has been reported that 61.2%-87% of patients who harbor TCs are women [5,6,30,48,50]. We found that this number was 74.8% in case reports and 90% in our EMG study.…”
Section: Prevalencesupporting
confidence: 61%
See 1 more Smart Citation
“…It has been reported that 61.2%-87% of patients who harbor TCs are women [5,6,30,48,50]. We found that this number was 74.8% in case reports and 90% in our EMG study.…”
Section: Prevalencesupporting
confidence: 61%
“…Therefore, small TCs may have been overlooked. MRI studies of the lumbosacral spine that accounted for small cyst sizes have reported a prevalence of 9.1%-10.6 % [15,50].…”
Section: Prevalencementioning
confidence: 99%
“…The reported prevalence partly depends on cyst size from which lesions were labeled TC. Patients often have multiple cysts, and more women than men harbor symptomatic TC . One‐fifth of the TC were found to be symptomatic .…”
Section: Discussionmentioning
confidence: 99%
“…Many case reports, as well as experience with large series, have been reported in the literature. Despite a considerable number of scientific publications, this clinical entity remains controversial, and TC are almost always thought to be unrelated to the patient's symptoms . Yet the pathological entity “symptomatic Tarlov cysts (STC),” is well defined and includes progressive debilitating sacral, ischial, and pelvic pain, neurological symptoms, bladder, sexual, and bowel disorders .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation